Exporter Performance in the German Business Services Sector: First Evidence from the Services Statistics Panel - Vogel, Alexander (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
A wide range of empirical studies has analysed exporter performance, especially the relationship between exports and productivity in the manufacturing sector. By contrast, a detailed investigation of the services sector has remained largely neglected. To close this gap, this paper focuses on the relationship between exports and several performance characteristics in the German business services sector—average wage, productivity, size and turnover profitability—in order to determine whether export premia and self-selection into export markets exist in the business services sector. To ensure the comparability of the results with those from the manufacturing sector, empirical models used to analyse the manufacturing sector are transferred to investigate the business services.
Keywords: Export; Business Service; 330 Wirtschaft